The historical hermeneutics and the importance of explain the world history from Mexico (2011)
In this paper I argue that Latin America accepts a worldview developed in Europe. This worldview was conceived during the nineteenth and twentieth centuries, and it serves the interests of one small part of the world. It is not useful to adequately explai